2007
DOI: 10.1258/095646207780658962
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of primary HIV-1 drug resistance in pregnant women and in newly diagnosed adults at Tijuana General Hospital, Baja California, Mexico

Abstract: At Tijuana General Hospital, between March 2003 and June 2005, pregnant women and other adults, recently identified as HIV infected, antiretroviral naïve, were enrolled to examine the prevalence of primary HIV drug resistance. All subjects had the Calypte HIV-1 BED Incidence enzyme immunoassay test to identify recent infection. Genotypic analysis of HIV-1 protease and reverse transcriptase regions in plasma was performed. Forty-six subjects participated, eight (17%) men, 38 (83%) women. Ten (22%) subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In a previous report based on a smaller number of naïve patients from Venezuela (Bouchard et al 2007), the prevalence of mutations conferring drug resistance (2/20, 10%) was found to be very similar to that observed in the current study (11%). The prevalence of drug resistance mutations among viruses infecting naïve Venezuelan patients was higher than those reported in Argentina and Mexico (4.2% and 2.5%, respectively) (Dilernia et al 2007, Viani et al 2007). In Brazil, primary resistance mutations vary according to region, with low prevalence in Rio de Janeiro (1.4%) (Varella et al 2007) and higher prevalence in Sao Paulo (6.5%) (Gonsalez et al 2007).…”
mentioning
confidence: 62%
“…In a previous report based on a smaller number of naïve patients from Venezuela (Bouchard et al 2007), the prevalence of mutations conferring drug resistance (2/20, 10%) was found to be very similar to that observed in the current study (11%). The prevalence of drug resistance mutations among viruses infecting naïve Venezuelan patients was higher than those reported in Argentina and Mexico (4.2% and 2.5%, respectively) (Dilernia et al 2007, Viani et al 2007). In Brazil, primary resistance mutations vary according to region, with low prevalence in Rio de Janeiro (1.4%) (Varella et al 2007) and higher prevalence in Sao Paulo (6.5%) (Gonsalez et al 2007).…”
mentioning
confidence: 62%
“…In both cases, most TDR cases were associated with NRTI. A study performed from 2003 to 2005 in the city of Tijuana, in the Northwest region at the border with the USA, reported low TDR levels (n = 41, 2.5%), associated with NRTI [ 47 ]. More recent studies have reported moderate TDR levels in the country.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17] Few studies have been conducted in Latin America concerning the prevalence of TDR, and available studies report TDR prevalences from 3% to 16%. [17][18][19][20][21][22][23][24] In the Central American region there is scant information regarding TDR, but one study reported a 9.2% prevalence of TDR in Honduras at the beginning of the national antiretroviral therapy program during 2002-2003. 25 TDR represents a public health concern since it reduces the number of effective antiretroviral medications available to infected persons and therefore increases the risk of treatment failure.…”
Section: Introductionmentioning
confidence: 99%